Preschooler Social And Emotional Development During the Covid-19 Pandemic: Perkembangan Sosial dan Emosional Anak Prasekolah selama Pandemi Covid-19 - Widyastuti (Universitas Muhammadiyah Sidoarjo, 2023)
Pre-schoolers’ social and emotional development has impacted by Covid-19 pandemic. The pandemic has limited their activities. This study aims to narratively review various articles related to the social and emotional development problems of children affected by the COVID-19 pandemic and to find out its factors. Article reviews is used to collect data related to pre-schoolers social and emotional development and its factors during the pandemic. The result indicates that there are several psychological problems on pre-schoolers, namely anxiety, attachment issues, and maladaptive behaviour. The research also includes pre-schoolers’ social and emotional development moderating factors, namely parent belief, parenting stress, parenting efficacy, and school management. This research implies that boosting parent and school competencies to create playful and connected circumstances can help pre-schoolers’ develop their social and emotional competence. Highlights: The COVID-19 pandemic has negatively affected pre-schoolers' social and emotional development. Psychological issues, including anxiety and attachment issues, have emerged among pre-schoolers during the pandemic. Parental beliefs, parenting stress, and school management play crucial roles in moderating pre-schoolers' social and emotional development during these challenging times. Keywords: Pandemic covid-19, Preschool, Socioemotional Development